Penerapan Penyuluhan dengan Metoda Ceramah disertai Demontrasi untuk Merubah Pengetahuan, Sikap dan Keterampilan Mencuci Tangan Memakai Sabun Siswa SD Negeri Pujokusuman 1 Kota Yogyakarta - Citra Nuraida; M. Mirza Fauzie; Purwanto Purwanto (Poltekkes Kemenkes Yogyakarta, 2015)
Educating the values of clean and healthy life behavior in schools is an absolute need, since various diseases which often attack school aged children are generally have correlation with this behavior. Results from of a preliminary test by administering questionnaire to 30 grade IV students of Pujokusuman 1 Elementary School, revealed that 70 % did not know the 12 steps of good hand-washing and 60 % did not know what diseases can be prevented by handwashing. The study was aimed to determine the influence of elucidation combined with demonstration method for those elementary school students’ knowledge, attitude and practice about handwashing with soap. By conducting demonstration method, students can see, observe, hear, and probably can also feel the process that is shown. The study was a quasiexperiment with pretest post-test with control group design approach. Based on the result of independent t-test at 95 % level of significance, it was found that the difference in the improvement of attitude between the group with speech only and the group accompanied with demonstration was statistically significant. The results obtained from Mann-Whitney test also showed that the differrence escalation of knowledge and practice between both groups were significant. To conclude, elucidation combined with demonstration method to elementary school aged children, gave better improvement on the knowledge, attitude and practice about handwashing with soap.